2005
DOI: 10.1159/000082585
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of the Diagnosis of Natural Rubber Latex Allergy by the Basotest<sup>®</sup> Method

Abstract: Background: The flow cytometry CD63-based basophil activation test (Basotest®) has already been validated for the diagnosis of immediate-type allergy such as venom, house dust mite or cypress pollen allergies. The aim of this study was to evaluate the performance (specificity and sensitivity) of Basotest in the diagnosis of natural rubber latex allergy. Methods: We included 46 latex allergic patients (clinical symptoms of latex allergy, positive latex skin prick tests and/or latex specific IgE) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 31 publications
0
15
0
1
Order By: Relevance
“…Moreover, our results with DPT underline that false-positive results exist with CD63 as well as with CD203c. Up until recently, false-positive results in FC were unknown, they were described in the diagnosis of latex allergy [36].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our results with DPT underline that false-positive results exist with CD63 as well as with CD203c. Up until recently, false-positive results in FC were unknown, they were described in the diagnosis of latex allergy [36].…”
Section: Discussionmentioning
confidence: 99%
“…Many of these studies have been reviewed recently [8,9,10]. Herewith, tables 1, 2, 3, 4, 5, 6, 7summarize the results of validated clinical studies performed with various allergens such as inhalant allergens [25,26,27,28,29,30,31,32,33] (table 1), hymenoptera venoms [34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56] (table 2), latex [57,58,59,60,61,62,63] (table 3), food [64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80] (table 4) and drugs [81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99,100,101,…”
Section: Clinical Issues In the Diagnostic Use Of Batmentioning
confidence: 99%
“…In several validated studies [57,58,59,60,61,62,63] (table 3), BAT was shown to demonstrate a sensitivity and specificity for CD63 expression of >90%, with one exception in which sensitivity was reported to be 75% for CD203c and 50% for the CD63 assay [60]. BAT is the test which reflects the most closely clinical provocation.…”
Section: Clinical Indications Of Batmentioning
confidence: 99%
“…In most patients, diagnosis of NRL anaphylaxis can readily be established by quantification of sIgE (k82), skin tests, or both (77)(78)(79). Although these tests are highly reliable, results of are not always unequivocal (80), and some patients might need additional tests such as basophil activation (81)(82)(83) or challenge tests (84,85) to establish diagnosis.…”
Section: Natural Rubber Latexmentioning
confidence: 99%